Validation of match notation (A coding system) in tennis - Hizan, H.; Whipp, P. R.; Reid, M. (Journal of Quantitative Analysis in Sports, 2010)
The aim of this study was to establish the reliability and validity of a coding system for measuring serve and return of serve locations in tennis. A notational analysis of men`s and women`s singles matches at the 2008 Australian Open was undertaken. The results revealed that the inter-rater reports were highly similar on first or second serve (r=0.972), serve landing location (r=0.999), returner`s impact location (r=0.990) and return of serve landing location (r=0.995). Hawk-Eye data were used to validate the coding measures for ball location. When comparing the coded ball location data of the researcher (n=1) and tennis coaches (n=4) to Hawk-Eye data, high correlations for the landing location of the serve (r=0.998), the impact location of the return (r=0.993) and the landing location of the return of serve (r=0.997) were registered. The match notation system analysed was shown to be reliable and valid for the study of serve and return of serve strategies and tactics in tennis. This system also provides a template for other researchers and coaches to evaluate game tactics in tennis.